Perspectives of Heat Stroke Shield: An IoT based Solution for the Detection and Preliminary Treatment of Heat Stroke - Javed, S.; Ghazala, S.; Faseeha, U. (Engineering, Technology & Applied Science Research, 2020)
Heat stroke is considered a major problem in Karachi, with a considerable number of people recorded as victims each year. The proposed Internet-of-Things (IoT) based heat stroke shield works under heat stroke conditions, depending on a heat index value (atmospheric temperature and humidity). The system comprises of a wristband, a hardware kit and an alert system which can pre-notify a wearer regarding his body parameter readings. Moreover, the system can also work as a problem solver, in heat stroke condition, by showering water on the victim. In both cases, an alert will also be generated to the wearer’s caretakers with his GPS location.